Eye tracker as an implied social presence: awareness of being eye-tracked induces social-norm-based looking behaviour - Hoo Keat Wong; Ian D. Stephen (Journal of Eye Movement Research)
Human behaviour is not only influenced by the physical presence of others, but also implied social presence. According to Risko and Kingstone (2011), an eye tracker can represent an implied social presence which could influence individuals’ gaze behaviour. This study examines the impact of awareness of being eye-tracked on eye movement behaviour in a laboratory setting.  During a classic yes/no face recognition task, participants were made to believe that their eye movements were recorded (or not recorded) by eye trackers. Their looking patterns with and without the awareness of being eye-tracked were compared while perceiving social (faces, faces-and-bodies) and non-social (inanimate objects) video stimuli. Area-of-interest (AOI) analysis revealed that misinformed participants (who were not aware that their eye movements were being recorded) looked more at the body (chest and waist) compared to informed participants (who believed they were being eye-tracked), whereas informed participants fixated longer on the mouth and shorter on the eyes of female models than misinformed participants did. These findings highlight the potential impact of an awareness of being eye tracked on one’s eye movement pattern when perceiving a social stimulus. We therefore suggest that even within laboratory settings an eye tracker may function as an implied social presence that leads individuals to modify their eye movement behaviour according to socially-derived inhibitory norms.